Optimasi Penjadwalan Pada Layanan Kursus dengan Algoritme Genetika (Studi Kasus: Unit Pengembangan Bahasa Universitas Brawijaya) - Rio Cahyo Anggono; Imam Cholissodin; Edy Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Language Development Unit Universitas Brawijaya or Brawijaya Language Center (BLC)'s course service is one of the services most in demand by many people. The relatively cheap price and the schedule selection by each participant are the main factors why many people choose BLC. The lack in the BLC course service is from an administrative perspective. The course scheduling system is still done manually by the course administration. Therefore, it is necessary to conduct research related to course scheduling. In the future, this research can assist BLC in course scheduling. The method that will be used in this research is Genetic Algorithm. In this research, the genetic algorithm process includes initial population formation and chromosome representation, parent selection, crossover and mutation, calculation of fitness values, population replacement selection, and chromosome derepresentation. Based on the test results, the best parameter values are found in the population number 700, Cr 0.5, Mr 0.4, and the number of generations of 900 with a fitness value of 0.98182.